Digital transformation and sustainable performance: the role of management control system - Latif, Badar; Ong, Tze San; Mohd Said, Ridzwana; Muhammad, Haslinah; Abdul Hanan (Human Resource Management Academic Research Society, 2023)
In light of the emerging paradigm of digital transformation, this study aims to provide multiple contributions to the sustainable development literature. This study motivate to provide the implications for scholars and policymakers to amplify emerging trends in digital transformation. Despite the concept of digitalization is growing tremendously, research on digital transformation within the academic literature of sustainable performance appears unclear, especially in the context of Pakistani manufacturing industry. In line with DC theory and stakeholder theory, this study provided insights into a deeper understanding of utilizing digital transformation as essential intellectual capital for sustainable development. This study examines whether management control systems play a moderating role in the nexus between digital transformation and sustainable performance. The study collected data from 286 manufacturing companies in Pakistan by using a simple random sampling technique. To analyze the causal relationship, this study uses the SPSS software, which is innovative in the context of the digital transformation. The findings of this study added value to the current debate on digital transformation and create interesting implications for manufacturing sector, especially for managers, professionals and for government bodies. Besides, this research can shed lights to provide a holistic framework on digital transformation through MCS, which can open new avenues for the sustainable development of Pakistani manufacturing SMEs.